Comparison of the mitochondrial genomes of three geographical strains of Apis laboriosa indicates high genetic diversity in the black giant honeybee (Hymenoptera: Apidae). Issue 2 (1st February 2023) - Tang, Xiang‐You; Yao, Yu‐Xin; Li, Yao‐Hui; Song, Hua‐Li; Luo, Rui; Shi, Peng; Zhou, Ze‐Yang; Xu, Jin‐Shan
Abstract: Apis laboriosa is the largest honeybee that lives mainly on cliff faces, with strong migratory ability. In this study, we firstly sequenced and assembled two complete mitochondrial genomes of A. laboriosa isolated from two distant locations in China (Chongqing and Shangri‐La regions). Combined with the published mitochondrial genome of A. laboriosa from Nepal, comparative genomic analyses were conducted to gain insight into the genetic diversity of giant honeybees from different geographical distributions. The mitochondrial genomes of A. laboriosa from Chongqing and Shangri‐La regions were 15, 579 and 15, 683 bp in length, respectively, both larger than that from Nepal with the length of 15, 510 bp. Three mitochondrial genomes all harbor 37 common genes and present the same AT bias and the frequency of codon usage. However, the fragments including COX 1, SSUrRNA, LSUrRNA, and the AT‐rich region of the mitochondrial genome from Shangri‐La region demonstrate distinctive insertions and deletions compared to those from Chongqing and Nepal regions. Phylogenetic trees of mitochondrial genomes show that A. laboriosa from Chongqing is most closely related to that from Nepal, rather than to Shangri‐La. Genetic distance between Shangri‐La and Chongqing or Nepal was even larger than that between the various subspecies of Apis mellifera . Overall, these results unmark that A. laboriosa in different geographical distributions can exhibit high genetic diversity at the mitochondrial genomic level, and therein, A. laboriosa from Shangri‐La may be the subspecies. All these studies will contribute to our understanding of the geographical distribution and genetic differentiation of black giant honeybee in Asian region. Abstract : Overall, this study demonstrates that Apis laboriosa with different geographical distributions have rich genetic diversity at the mitochondrial level, where Apis laboriosa from Shangri‐La even reached the subspecies differentiation level. Meanwhile, our study also found that geographical distance is not the main reason for genetic differentiation, which provides a reference for further expanding research on the geographical distribution of Apis laboriosa and analyzing their mechanisms of genetic differentiation.